Novel Record Replacement Algorithm and Architecture for QoS Management over Local Area Networks - Tung, Yi-Chih; Law, Yuk-Wing; Hwang, Wen-Jyi; Tai, Tsung-Ming; Ho, Chih-Hsiang; Chen, Cheng-Chang (Micromachines (Basel), 2022)
An effective System-on-Chip (SoC) for smart Quality-of-Service (QoS) management over a virtual local area network (LAN) is presented in this study. The SoC is implemented by field programmable gate array (FPGA) for accelerating the delivery quality prediction for a service. The quality prediction is carried out by the general regression neural network (GRNN) algorithm based on a time-varying profile consisting of the past delivery records of the service. A novel record replacement algorithm is presented to update the profile, so that the bandwidth usage of the service can be effectively tracked by GRNN. Experimental results show that the SoC provides self-aware QoS management with low computation costs for applications over virtual LAN.